1991
DOI: 10.1021/bi00240a036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cysteine replacements at positions 13 and 50 on metallothionein structure

Abstract: Recombinant wild-type and mutant Chinese hamster metallothioneins, purified from the yeast Saccharomyces cerevisiae, were analyzed for their chemical and spectroscopic properties. The mutant proteins contain cysteine to tyrosine replacements at positions 13 and 50. Wild-type and mutant metallothioneins, in their cadmium-bound forms, all showed characteristic ultraviolet absorption spectra with shoulders at 245-250 nm due to cadmium-thiolate charge transfer. Upon acidification, these absorption shoulders were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
4
24
1
Order By: Relevance
“…5 E) and the complete lack of any correspondence of their CD spectrum with the calculated difference between the CD spectra of the Cd,-a,-fragment and the parent holoprotein suggest that the Cd-thiolate cluster in the Cd,-P-fragments has undergone a major transformation which we ascribe to the loss of Cys38 from the cluster. A similar large chiroptical change of a Cd-thiolate cluster has been reported earlier for recombinant Chinese hamster MT in which a metal-binding cysteine residue (CysSO) was replaced by tyrosine (Cismowski and Huang, 1991). Such large effects are believed to be the result of changes in the arrangement of the chromophoric thiolate ligands within the Cd-thiolate clusters and are thus a reflection of cluster geometry (Willner et al, 1992).…”
Section: Resultssupporting
confidence: 65%
“…5 E) and the complete lack of any correspondence of their CD spectrum with the calculated difference between the CD spectra of the Cd,-a,-fragment and the parent holoprotein suggest that the Cd-thiolate cluster in the Cd,-P-fragments has undergone a major transformation which we ascribe to the loss of Cys38 from the cluster. A similar large chiroptical change of a Cd-thiolate cluster has been reported earlier for recombinant Chinese hamster MT in which a metal-binding cysteine residue (CysSO) was replaced by tyrosine (Cismowski and Huang, 1991). Such large effects are believed to be the result of changes in the arrangement of the chromophoric thiolate ligands within the Cd-thiolate clusters and are thus a reflection of cluster geometry (Willner et al, 1992).…”
Section: Resultssupporting
confidence: 65%
“…We have suggested that this free thiol might be more reactive toward disulfides such as GSSG (4). Herein, we have used Ellman's reagent to investigate the redox behavior of MT, a reaction that has been studied earlier in some detail (13,14,34). Under the conditions of our experiments, the kinetic phase affected by ATP corresponds to the faster of the two phases ascribed by others to the reaction of the ␣-domain of MT (35).…”
Section: Discussionmentioning
confidence: 94%
“…The near-UV CD might be even better owing to its sensitivity to small perturbations of the environments of the aromatic side chains. Indeed, some researchers have used the near-UV CD for this purpose (Cismowski and Huang, 1991;Lin et at., 1992;van der Goot et al, 1993a,b;Patti et al, 1993), but a larger number have used the far-UV CD only. Ideally, both the near-and far-UV CD spectra should be used for comparing altered and wildtype proteins.…”
Section: A Structural Analysis Of Recombinant Native Proteins and Thmentioning
confidence: 99%